Formation of Mikhailo Grushevs'ky as a Historiographer (Gymnasium Time) - Тельвак В.П. (Видавничо-поліграфічний центр "Київський університет", 2007)
In the present paper on the broad basis of sources the grammar school period of M.Hrushevsky's life is analyzed from the standpoint of formation of his historiographic views. The origins of his world outlook and scientific interests' formation are investigated. Youth's first historical essays, diaries and fiction works are studied. The conclusion of M.Hrushevsky's romantic-rationalistic vision of Ukrainian historiography is made.

На основі широкої джерельної бази проаналізовано гімназійний період життя М. Грушевського під кутом формування його історіографічних поглядів. Досліджено джерела формування його світогляду і наукових інтересів. Розглянуто перші історичні реферати юнака, його щоденники і белетристика. Зроблено висновок про романтично-раціоналістичне бачення М. Грушевським української історіографії.
Формування Михайла Грушевського як історіографа (гімназійна доба)